A study on out of pocket expenditure among the urology patients covered under health schemes in a teaching hospital - Asheela, Safiyath; Qadiri, Ghulam Jeelani; Shet, Nagaraj; Sharma, Prajna (International Journal Of Community Medicine And Public Health, 2019)
Background: Health is one of the most important components of an effective poverty reduction strategy. However, use of health services is sometimes associated with out-of-pocket (OOP) payments. Urology disorders are often chronic and affect individuals not by shortening survival, but by impairing quality of life hence posing a substantial economic impact for patients. A well-planned health finance systems protects population against the financial risks of ill-health. This study addressed concerns over high levels of out-of-pocket payments even by those who have insurance coverage. Methods: Descriptive study was conducted among 160 patients admitted in Urology Department who are covered under various health schemes for the duration of 6 months. Results: Of the 160 study participants studied, 129 (80.62%) were males, 37 (23.13%), 64 (40%) were illiterates and most of the families 127 (79.38%) were from rural area. Various health schemes availed were, 120 (75%) Arogya Karnataka, 8 (11.25%) RBSY Kerala and 6 (3.75%) Sampoorna Suraksha. Expenses other than medical included home care assistance, adaptations to home and cost of parallel treatment. The main source for out of pocket expenditure was borrowing money from relatives or friends 70 (43.8%), self-finance 46 (28.7%) and selling valuables 28 (17.5%). Prevalence of catastrophic health expenditure in our study was 8.75%. Conclusions: The government should increase the public health spending to reduce the out of pocket expenditure by the families and the public must be educated about the availability of insurance scheme and their efficient/optimum utilization.